Perancangan Jaringan Fiber To The Home Berbasis Gigabit Passive Optical Network Di Citra Garden Puri Cluste Denza - Timothy Sutjipto, Marcellus; Octaviani, Sandra; Ghozali, Theresia; Windha Mahyastuty, Veronica; Kristina Yanti Hutapea, Duma (Prodi Teknik Elektro, Fakultas Teknik Unika Atma Jaya Jakarta, 2023)
This research aims to design a GPON-based Fiber to The Home (FTTH) line in the Citra Garden Puri cluster Denza . The method used is to carry out field observations, by conducting surveys to determine the need for equipment that will be used in designing the route. After the survey is conducted, this project requires Google Earth Pro software to do the mapping of the spot that is used for the ODP and to create passages for the fiber. To make sure that all planning already meets the requirement, there are several calculationdone in this research such as; link loss budget, power link budget, power margin and risetime budget. The distance that were used in the calculation are calculated from the STO Cengkareng until the ONT on each customer. Based on the calculation, the result of the biggest loss for link loss budget are obtained from the upstream, in the amount of 22,0456 dB and the loss from downstream are equals to 21,5721 dB. The result that obtained for the upstream loss of power link budget are equals to -17,0456 dBm and -16,5172 dBm for downstream. The next calculation is power margin, from this project we obtained the lowest power margin for the upstream 6,9544 dB and 7,4288 dB for downstream. The last calculation obtained for this project is rise time budget, from the calculation the shortest data for the rise time budget upstream is 0,1001 ns and for the downstream is 0,1019 ns. Based on all the calculation, this project can be concluded as a success because all the calculation are between the boundary that is tolerated by PT Telkom.